Formulation, processing and water stability of pelleted feeds with varying levels of protein used in carp nutrition studies - Varghese, T.J., Renukaradhya, K.M. and (Fishery Technology, 2021)
Four dry pelleted feeds containing 20%, 30%, 40% and 45% protein were formulated incorporating casein as the main source of protein for use in carp nutrition studies. The caloric content in all the feeds was maintained constant. The method of processing is described. The formulated diets were tested for water stability. This test has revealed that the diet containing 20%, 30% and 40% protein had better stability than that containing 45% protein. This was due to the relatively higher fat content in the former three diets. However, all the feeds were sufficiently stable at the end of one hour in which time carps are known to utilise supplementary diets.